From Andalusia to Nusantara: Intellectual Transfer in the Long Journey of Islamic Civilization - Magfiroh, Diana (Sekolah Tinggi Agama Islam Kuningan, 2025)
The long journey of Islamic civilization shows that the transmission of knowledge did not only take place in the Middle East, but also included a trajectory from Andalusia to the Islamic East, including the archipelago. Andalusia as the intellectual center of Islam in the West played an important role in producing monumental works in the fields of philosophy, Sufism, and Islamic law which later influenced the mindset and religious practices in other regions. This research aims to identify and analyze the process of intellectual transfer from Andalusia to Nusantara through the network of scholars, classical works, and Islamic educational institutions. Using a historical qualitative approach and hermeneutic analysis techniques, this research traces the intellectual traces of Andalusian figures and the transformation of their ideas in the local context of the archipelago through manuscripts, scholarly sanads, and cultural adaptations. Data were collected through literature study, manuscript analysis, and network mapping of scholars. The results showed that the process of knowledge transfer took place through transnational intellectual pathways involving civilization nodes such as Cairo, Baghdad, and Delhi, before reaching scholarly centers in the archipelago such as Aceh and Java. The main ideas of thinkers such as Ibn Rushd and Ibn Arabi were localized in the form of poetry, suluk, and yellow books. Islam Nusantara thus proves to be a synthesis of global intellectual traditions and local culture, confirming its strategic position in the world's Islamic civilization.